2021
DOI: 10.1002/mawe.202100032
|View full text |Cite
|
Sign up to set email alerts
|

Thermally sprayed coatings for the valve industry

Abstract: In dieser Studie wird die Entwicklung verschiedener thermisch gespritzter Beschichtungen für den Einsatz im Armaturenbau diskutiert. Basierend auf etablierten Verschleißschutzschichten der Armaturenindustrie wurden verschiedene Festschmierstoffe in diese Beschichtungen integriert, um das Verschleiß-und Reibungsverhalten bei anwendungsnahen Belastungen für Armaturen zu verbessern. Für die Anwendungen wurden Verschleißschutzschichten auf Basis von WC/CoCr und Cr 3 C 2 /NiCr entwickelt. Als Festschmierstoffe wurd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…With the coating P--, a promising process point was identified which should be used in future to develop new types of coatings for the valve industry. In previous studies (Ref 4,20,21), it was shown that the integration of solid lubricants reduces the wear of conventionally used valve coatings. In subsequent studies, the integration of solid lubricants into HVAF-sprayed fine feedstock material coatings will be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…With the coating P--, a promising process point was identified which should be used in future to develop new types of coatings for the valve industry. In previous studies (Ref 4,20,21), it was shown that the integration of solid lubricants reduces the wear of conventionally used valve coatings. In subsequent studies, the integration of solid lubricants into HVAF-sprayed fine feedstock material coatings will be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For a reference feedstock, the commercial 86WC/10Co4Cr powder Amperit 507.059 from Ho ¨gana ¨s (Du ¨sseldorf, Germany) is chosen. The carbide sizes in this commercial powder extend into the ultra-fine scale of Ø WC & 200-400 nm with a particle size distribution of d10/d50/ d90 = 11 lm/18 lm/29 lm and an apparent bulk density of q = 5.8 g/cm 3 .…”
Section: Experimental Procedures Feedstock Materialsmentioning
confidence: 99%